Prarancangan Pabrik Metil Metakrilat Dari Aseton SianohidrinKapasitas 65.000 Ton/Tahun - Kusumandari, Dwi Sapta; , Ir.Herry Purnama, M.T., Ph.D; , Eni Budiyati, S.T, M.Eng (2016)
Methyl methacrylate plant design using raw materials acetone cyanohydrin, methanol and sulfuric acid with a capacity of 65,000 tons / year. The process of making methyl methacrylate was made through two stages, the first is hydrolysis, acetone cyanohydrin with sulfuric acid into metakrilamid sulfate. The reaction takes place in the liquid phase, irreversible, exothermic processed in continuous stirred-tank reactor (CSTR). The second stage reaction is metakrilamid sulfate esterification reaction with methanol to form methyl methacrylate. The reaction takes place in the liquid phase, irreversible, exothermic processed in CSTR. Factories produce methyl methacrylate as much 8192.2680 kg / hr that require raw materials acetone cyanohydrin as 7.4969,6280 kg/hour, as much sulfuric acid 13665.9821 kg/hour, and methanol as 8203.1423 kg/hour. Utilities required includes 1,634,177.4051 kg/hour of cooling water, water for steam needs of 14,600,6596 kg/hour produced from boiler, fuel 230,200,0467 kg/day, the electricity needs of 750 kW was obtained from the Perusahaan Listrik Negara (PLN) and provided with a generator set as a backup, as well as compressed air requirement of 76.14 m3 /h. Methyl methacrylate factory stands on an area of 20,000 m2 are planned to be built in Gresik regency, East Java province in 2019 with the economic analysis results as follows: Number of Fixed Capital Investment of Rp. 422,107,111,548.62, Percent Return On Investment before tax of 35.20 % and after tax of 24.64 %, Pay Out Time before tax for 2.2 years, while after tax for 2.9 years, Break Even Point by 56 , 75%, Shut Down Point amounted to 41.54%, dan Discounted Cash Flow amounted to 26.02%. Based on the data above, it is feasible to set up factories.